THE LIFE COURSE: MIDTERM EXAMINATION SOCI 361/461 (Take home) - Dannefer, Dale; Patterson, Robin (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This is a compilation of teaching resources on The Life Course. The life course refers to the structure and patterning of individual lives, which are always both situated yet never reducible to the constraints of those situations. No individual can be understood without reference to the specific socio-historical context they occupy. Both recent developments and classic themes are evident throughout the syllabi in this collection. Some scholars give more attention to individual-level processes and others to the institutional level; some focus on the ways in which historical changes produce unique life histories and cohort differences; others focus on the structural framework of the institutionalized life course. The set also includes a number of materials from international colleagues. This both reflects and generates increasing sensitivities and commitments to understanding cross-cultural questions about the life course, the growing importance of globalization in shaping the individual life course, and the impact of social policy in the structuring of the life course at the macro level. Materials on closely related topics are also included.